2021
DOI: 10.1200/go.20.00621
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in De Novo Metastatic Renal Cell Carcinoma: A Report From the Latin American Renal Cancer Group

Abstract: PURPOSE To assess the effect of clinical and pathological variables on cancer-specific and overall survival (OS) in de novo metastatic patients from a collaborative of primarily Latin American countries. PATIENTS AND METHODS Of 4,060 patients with renal cell carcinoma diagnosed between 1990 and 2015, a total of 530 (14.5%) had metastasis at clinical presentation. Relationships between clinical and pathological parameters and treatment-related outcomes were analyzed by Cox regression and the log-rank method. RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
1
Order By: Relevance
“…A few previous studies suggested that a larger primary renal tumor size may be negatively associated with the prognosis of patients with mRCC who underwent CN, although the results have not been conclusive. 21,22 Another study reported that pathological perirenal fat invasion in the primary renal tumor was independently associated with worse overall survival, 23 although it should be noted that immediate CN has been utilized less frequently in recent clinical practice and the availability of pathological findings of primary renal tumors is limited. Renal mass biopsy can also provide pathological information; however, biopsy specimens cannot represent the whole tumor characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A few previous studies suggested that a larger primary renal tumor size may be negatively associated with the prognosis of patients with mRCC who underwent CN, although the results have not been conclusive. 21,22 Another study reported that pathological perirenal fat invasion in the primary renal tumor was independently associated with worse overall survival, 23 although it should be noted that immediate CN has been utilized less frequently in recent clinical practice and the availability of pathological findings of primary renal tumors is limited. Renal mass biopsy can also provide pathological information; however, biopsy specimens cannot represent the whole tumor characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…En Latinoamérica, 14.5% de los CRCC se diagnostican de novo con una enfermedad avanzada, y del 20-30% presentarán una recurrencia de la enfermedad, de las cuales 90% se presentarán dentro de los primeros cinco años. 1 A través de las nuevas estrategias de manejo sistémico basadas en el bloqueo de la angiogénesis con inhibidores de tirosina quinasa (TKI, por sus siglas en inglés) y la inhibición de puntos de control inmune (ICP, por sus siglas en inglés), la supervivencia global (SG) media del CRCC avanzado ha aumentado de seis meses a más de cuatro años. 2,3 Al momento del diagnóstico de una enfermedad avanzada, el riesgo pronóstico es un criterio clave a tomar en cuenta en la elección de la primera línea de tratamiento.…”
Section: Generalidadesunclassified
“…Survival rates of RCC patients depend on stage, and 30% of patients in Brazil already have metastatic disease at diagnosis (Padala et al 2020 ; Abreu et al 2021 ; Bahadoram et al 2022 ; Tran and Ornstein 2022 ). Treatment for metastatic disease has evolved in recent years due to the use of new immune combinations, such as ICIs or ICIs plus TKIs, which improve the response rate and overall survival (OS) (Rassy et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%